Liquid-phase synthesis of a Li3PS4 solid electrolyte using ethyl isobutyrate as a synthetic medium - Minh Nguyet, Nguyen Thi; Anh, Luu Tuan; Toan, Tran Viet; Tu, Tran Anh; Quynh Anh, Luong Thi; Huy Phuc, Nguyen Huu (Frontiers in Energy Research, 2024)
A β-Li3PS4 solid electrolyte was prepared via liquid-phase synthesis using ethyl isobutyrate as a synthetic medium. The precursor and solid electrolyte structures were characterized using thermogravimetry-differential thermal analysis and X-ray diffraction techniques. The dielectric relaxation analysis showed two relaxation regions, which revealed a bulk and grain boundary ionic migration process. At a temperature lower than 90℃, the frequency dependence of the dielectric constant of the prepared sample was different from that of glassy Li3PS4, indicating that the motion of the PS4 unit enhances the ionic conductivity of the Li3PS4 solid electrolyte. The ionic conductivities of the cold-pressed and warm-pressed pellets at 25℃ were 6.8 × 10 -5 Scm -1 and 3.6 × 10 -4 Scm -1 , respectively.